Gender representation in selected post-Marcos plays in the Philippines / Mahtab Mahdavifar - Mahtab , Mahdavifar (2021)
This thesis focuses on women involvement as theater practitioners (actresses, directors and playwrights) in Filipino Theater in the time and after Marcos regime (1960-2000) with the focus on two main theater associations Philippines Educational Theater Association (PETA) and Philippines Repertory (REP). Moreover, it aims to shed light on the representation of women in the selected modern plays written in English by post- Marcos dramatists namely Jessica Hagedorn, Linda Faigao-Hall and Malou Leviste Jacob in their plays Dogeaters (1990), The Female Heart (2013) and A Significant Life (2000). In addition, the study also aims to find the ways and dominant techniques through which the post-Marcos dramatists and directors depicted women, their roles and their contribution to social changes. Furthermore, this study tries to explore the traces of gender performativity, which is defined as “the stylized repetition of acts” by American feminist Judith Butler (2011, p. 179) as a key element in breaking the traditional representation of women on stage and in print. In order to achieve this, Brechtian theories in drama and performance were employed.